Generalized LCM based counting functions - Shonhiwa, Temba (Utilitas Mathematica, 1999)
The aim of this paper is to investigate counting functions based on conditions involving the least common multiple of an m-tuple. Number-theoretic as well as combinatorial arguments are used to obtain some of our results.